# Use the quadratic formula. 2x2+ 9x-5=0

QUESTION POSTED AT 26/03/2020 - 01:05 PM

QUESTION POSTED AT 26/03/2020 - 01:05 PM

This should be the answer. Hope this helps

T²+ 2t + 1 = 0

a=1, b=2 & c=1 The formula is x'=[-b+√(b²-4ac)]/(2a)

and====================>x"=[-b-√(b²-4ac)]/(2a)

x' = [-2+√(2²-4(1)] / 2(1) ===> x' = -2/2 ==> x' =-1 & x" = -1

x'=x"= -1

a=1, b=2 & c=1 The formula is x'=[-b+√(b²-4ac)]/(2a)

and====================>x"=[-b-√(b²-4ac)]/(2a)

x' = [-2+√(2²-4(1)] / 2(1) ===> x' = -2/2 ==> x' =-1 & x" = -1

x'=x"= -1

ANSWERED AT 01/04/2020 - 01:40 PM

QUESTION POSTED AT 01/04/2020 - 01:40 PM

4 +- √16 - 4(2)(1) / 4 --> 4 +- √8 / 4 --> 4 +- 2√2 / 4 --> 2 +- √2/2

Ans: 2 + √2/2 and 2 - √2/2

Ans: 2 + √2/2 and 2 - √2/2

ANSWERED AT 01/04/2020 - 01:19 PM

QUESTION POSTED AT 01/04/2020 - 01:19 PM

To write the coefficients of the 8 terms, either start with a combination of 7 things taken 0 at a time and continue to 7 things taken 7 at a time or use the 7th row of Pascal’s triangle.

For the first term, write x to the 7th power and 3 to the 0 power. Then decrease the power on x and increase the power on y until you reach x to the 0 and y to the 7.

Simplify by evaluating the coefficients and powers of 3.

ANSWERED AT 01/04/2020 - 01:14 PM

QUESTION POSTED AT 01/04/2020 - 01:14 PM

A₁ = 1 = 4⁰

a₂ = 4 =4¹

a₃ =4 x 4=4²

a₄ =4 x 4² =4³

...................

...................

a(n) = 4⁽ⁿ⁻¹⁾

a₂ = 4 =4¹

a₃ =4 x 4=4²

a₄ =4 x 4² =4³

...................

...................

a(n) = 4⁽ⁿ⁻¹⁾

ANSWERED AT 31/03/2020 - 10:44 AM

QUESTION POSTED AT 31/03/2020 - 10:44 AM

Common denominator:

(r-2g)/g =-8j/g==> r-2g=-8j

Solve for j, ==> -8j = r-2g & j=(r-g)/(-8) or j= (g-r)/8

(r-2g)/g =-8j/g==> r-2g=-8j

Solve for j, ==> -8j = r-2g & j=(r-g)/(-8) or j= (g-r)/8

ANSWERED AT 31/03/2020 - 10:42 AM

QUESTION POSTED AT 31/03/2020 - 10:42 AM

(1) To find the angle between v and positive x-axis, we first determine the angle formed by v and the negative x-axis. Since v = (-7,8), its vertical measure y is 8 units and horizontal measure x is 7 units.

arctan(8/7) = 48.81°

Solving for angle between v and positive x-axis:

180° - 48.81° = 131.19°

(2) v1 x v2=|v1||v2|cosθ

Calculating for the dot product of the vector:

v1 x v2 = -7*1 + 8*0 = -7

Calculating vector magnitude:

|v1| = √(-7²+8²) = √113

|v2| = √(1²+0²) =1

cosθ = (v1 x v2) /|v1||v2| = -7/(√113 *1) = -0.659

arctan(8/7) = 48.81°

Solving for angle between v and positive x-axis:

180° - 48.81° = 131.19°

(2) v1 x v2=|v1||v2|cosθ

Calculating for the dot product of the vector:

v1 x v2 = -7*1 + 8*0 = -7

Calculating vector magnitude:

|v1| = √(-7²+8²) = √113

|v2| = √(1²+0²) =1

cosθ = (v1 x v2) /|v1||v2| = -7/(√113 *1) = -0.659

ANSWERED AT 30/03/2020 - 01:28 AM

QUESTION POSTED AT 30/03/2020 - 01:28 AM

**Answer:**

the answer is D (22)

**Step-by-step explanation:**

ANSWERED AT 29/03/2020 - 06:31 PM

QUESTION POSTED AT 29/03/2020 - 06:31 PM

8 translation: narrow or compress graph by a scale factor of 8

-6 translation: shift graph 6 points right

-6 translation: shift graph 6 points right

ANSWERED AT 28/03/2020 - 12:49 PM

QUESTION POSTED AT 28/03/2020 - 12:49 PM

v(x)=(s/t)

= (3x - 6) / (-3x+6)

= [3(x-2)] / [-3(x-2)] --> 3 is factored out

= 1/-1 ---> common terms are cancelled out.

= -1 ---> This is the
simplified formula.

To find the domain, we equate the denominator to 0.

-3x+6 = 0

3x = 6

x = 2

Domain: all values except 2.

w(x)=(t/s)(x)

= (-3x+6)x / (3x-6)

= [-3x(x-2)] / [3(x-2)] --> 3 is factored out

= -x --> The common terms are cancelled out. This is the simplified formula.

Solving for domain:

3x-6 = 0

3x = 6

x = 2

Domain: all values except 2.

ANSWERED AT 28/03/2020 - 12:27 PM

QUESTION POSTED AT 28/03/2020 - 12:27 PM

**Answer:**

Option B is correct

** ; **

**Step-by-step explanation:**

The recursive formula for the arithmetic sequence is given by:

.....[1]

where,

d is the common difference.

n is the number of terms.

**As per the statement:**

Paige borrows $700 from her parents for a new computer.

She repays $100 the first month, then begins to repay her parents $75 per month.

Now, she only has to pay back after then, $700 - $100 = $600

then, begins to repay her parents $75 per month.

**The sequence we get;**

600, 525, 450, ....

This is the arithmetic sequence.

here,

and d = -75

Since,

525-600 = -75

450-525 = -75 and so on...

Substitute the given values in [1] we have;

**Therefore, the recursive formula models the total amount of money still owed is:**

** ; **

ANSWERED AT 28/03/2020 - 12:25 PM

QUESTION POSTED AT 28/03/2020 - 12:25 PM

Your anser you have in there is correct:)

ANSWERED AT 28/03/2020 - 12:14 PM

QUESTION POSTED AT 28/03/2020 - 12:14 PM

Option: C is the correct answer.

C.

The sequence is given by the explicit formula as:

where is the nth term of the sequence.

Also, the first term of the sequence is:

i.e.

Also,

** Hence, the recursive formula which represents the same sequence is:**

** Option: C**

ANSWERED AT 28/03/2020 - 12:08 PM

QUESTION POSTED AT 28/03/2020 - 12:08 PM

I would start in the square root, do the parentheses first in the square root, then divide what you got in the square root by the 2x and when you do that you either add or subtract (depending on if the answer you got is positive or negative) to the negative 48. That helpful at all???

ANSWERED AT 28/03/2020 - 12:06 PM

QUESTION POSTED AT 28/03/2020 - 12:06 PM

**Answer:**

Option B - ** **

**Step-by-step explanation:**

Given : **Sequence 5, 13, 29, 61, 125, ...**

**To find : **Which recursive formula describes the sequence below?

**Solution :**

To find which function gives recursive formula substitute the value and check which satisfy the given sequence.

**A.**

Finding 2 term put n=2

Applicable as second term is 13.

Check for third term put n=3

**Not applicable as third term is 29**.

**B. **

Finding 2 term put n=2

Applicable as second term is 13.

Check for third term put n=3

**Applicable as third term is 29.**

**C. **

Finding 2 term put n=2

Applicable as second term is 13.

Check for third term put n=3

**Not applicable as third term is 29.**

**D.**

Finding 2 term put n=2

Applicable as second term is 13.

Check for third term put n=3

**Not applicable as third term is 29.**

**Therefore, Only Option B is correct **as it form the recursive formula of given sequence.

ANSWERED AT 28/03/2020 - 12:02 PM

QUESTION POSTED AT 28/03/2020 - 12:02 PM

The given sequence is x-1, -2x+2, 4x-4, -8x+8 .

Notice that this is a geometric sequence because here we have equal common ratio.

So, common ratio : r =

=

= Take out -2 as common factor

= -2 Cancel out x - 1.

The formula for general term of a geometric sequence is,

Where, first term:

We need to find the 10th term of this sequence. So, n = 10.

Next step is to plug in these values in the above formula to get the 10th term. Hence,

So, A is the correct choice.

ANSWERED AT 28/03/2020 - 11:58 AM

QUESTION POSTED AT 28/03/2020 - 11:58 AM

Which is the correctly balanced equation for the reaction of rust, Fe2O3, and hydrochloric acid, HCl? A. Fe2O3 + HCl → FeCl3 + H2O B. Fe2O3 +3 HCl → 2 FeCl3 + H2O C. Fe2O3 + 6...

ANSWERED AT 28/03/2020 - 11:51 AM

QUESTION POSTED AT 28/03/2020 - 11:51 AM

From the 6000 bacteria, it grew to 7800 bacteria after 4 hours. The increased in 4 hrs was 1800 bacteria, so we can say that there are 450 bacteria growing per hour. After 18 hrs, we can predict that there will be 14,000 bacteria will be present in the culture.

ANSWERED AT 28/03/2020 - 11:33 AM

QUESTION POSTED AT 28/03/2020 - 11:33 AM

**Answer:**

d

**Step-by-step explanation:**

A= (1.5 2) rr

ANSWERED AT 28/03/2020 - 11:25 AM

QUESTION POSTED AT 28/03/2020 - 11:25 AM

A(sub2) = 5 * 5^(2-1)

a(sub2) = 5 * 5^1

a(sub2) = 5 * 5

a(sub2) = 25

a(sub2) = 5 * 5^1

a(sub2) = 5 * 5

a(sub2) = 25

ANSWERED AT 28/03/2020 - 11:20 AM

QUESTION POSTED AT 28/03/2020 - 11:20 AM

2 * 6^(n-1)

a(sub4) = 2 * 6^(4-1)

a(sub4) = 2 * 6^3

a(sub4) = 2 * 216

a(sub4) = 432

a(sub4) = 2 * 6^(4-1)

a(sub4) = 2 * 6^3

a(sub4) = 2 * 216

a(sub4) = 432

ANSWERED AT 28/03/2020 - 11:11 AM

QUESTION POSTED AT 28/03/2020 - 11:11 AM

Where is the rest of the question

ANSWERED AT 28/03/2020 - 10:53 AM

QUESTION POSTED AT 28/03/2020 - 10:53 AM

I believe the answer is the first a

ANSWERED AT 28/03/2020 - 10:39 AM

QUESTION POSTED AT 28/03/2020 - 10:39 AM

I have to say C. Exponential

ANSWERED AT 28/03/2020 - 10:31 AM

QUESTION POSTED AT 28/03/2020 - 10:31 AM

((−2x^2)(x^3))(y)

**=****−****2****x^5****y**

Hope this helps

Good luck mate :P

Hope this helps

Good luck mate :P

ANSWERED AT 27/03/2020 - 01:00 PM

QUESTION POSTED AT 27/03/2020 - 01:00 PM

surface area=4πr2=2700 cm2

r2=27004π=27004×3=225

r=225−−−√=15

volume=43πr3=43×3×153=13500 cm3

r2=27004π=27004×3=225

r=225−−−√=15

volume=43πr3=43×3×153=13500 cm3

ANSWERED AT 27/03/2020 - 12:42 PM

QUESTION POSTED AT 27/03/2020 - 12:42 PM

To find the average rate of change of given function f(x) on a given interval (a,b):

Find f(b)-f(a), b-a, and then divide your result for f(b)-f(a) by your result for b-a:

f(b) - f(a)

------------

b-a

Here your function is f(x) = x^2 - 2x + 3. Substituting b=5 and a=-2,

f(5) = 5^2 -2(5)+3 =? and f(-2) = (-2)^2 - 2(-2) + 3 = ?

Calculate f(5) - [ f(-2) ]

------------------ using your results, above.

5 - [-2]

Your answer to this, if done correctly, is the "average rate of change of the function f(x) = x^2+2x+3 on the interval [-2,5]."

Find f(b)-f(a), b-a, and then divide your result for f(b)-f(a) by your result for b-a:

f(b) - f(a)

------------

b-a

Here your function is f(x) = x^2 - 2x + 3. Substituting b=5 and a=-2,

f(5) = 5^2 -2(5)+3 =? and f(-2) = (-2)^2 - 2(-2) + 3 = ?

Calculate f(5) - [ f(-2) ]

------------------ using your results, above.

5 - [-2]

Your answer to this, if done correctly, is the "average rate of change of the function f(x) = x^2+2x+3 on the interval [-2,5]."

ANSWERED AT 27/03/2020 - 12:26 PM

QUESTION POSTED AT 27/03/2020 - 12:26 PM

B quadratic no problem

ANSWERED AT 27/03/2020 - 09:49 AM

QUESTION POSTED AT 27/03/2020 - 09:49 AM

**Answer:**

To find the celsius temperature substitute 86 for F in the formula. Then use the order of operations to simplify. Substract 32 from 86. Then multiply 5 9 by 54 to get 30°C.

**Step-by-step explanation:**

ANSWERED AT 27/03/2020 - 09:46 AM

QUESTION POSTED AT 27/03/2020 - 09:46 AM

Since no example is being given, let's take for instance 2 functions, one quadratic & the second linear:

y₁=ax²+bx+c & the second y₂=mx+b

The solution of those function is the coordinates (x,y) where both meet at a point . In this case (& in all other cases) you have to state that y₁=y₂

ax²+bx+c = mx + b & solve

example

y₁= x²+3x-1 & y₂=x-2

x²+3x-1 = x-2==>x²+3x-1-x+2 = x²+2x+1

Find the root of x²+2x+1 & you will find x'=x" -1

We have found the value of x= - 1, to find y, just plug into any of the equation x by its value & you will find y=-3

So the solution of this system of equation is at their pint(s) of intersection, that is (-1,-3)

y₁=ax²+bx+c & the second y₂=mx+b

The solution of those function is the coordinates (x,y) where both meet at a point . In this case (& in all other cases) you have to state that y₁=y₂

ax²+bx+c = mx + b & solve

example

y₁= x²+3x-1 & y₂=x-2

x²+3x-1 = x-2==>x²+3x-1-x+2 = x²+2x+1

Find the root of x²+2x+1 & you will find x'=x" -1

We have found the value of x= - 1, to find y, just plug into any of the equation x by its value & you will find y=-3

So the solution of this system of equation is at their pint(s) of intersection, that is (-1,-3)

ANSWERED AT 27/03/2020 - 09:40 AM

QUESTION POSTED AT 27/03/2020 - 09:40 AM

Heron's formula:

Triangle Area =√[s(s-a)(s-b)(s-c)]

Where s = half of the perimeter of the triangle (in our case =36/2=18)

a, b, & c the length of each side (in our case all sides are equal since it's an equilateral triangle with a perimeter = 36 or each side =36/3 =12)

Now we can apply Heron's formula:

Area =√[18(18-12)(18-12)(18-12] =√[18x6x6x6] =√(3888) = 62.354 cm²

or rounded =62 cm²

Triangle Area =√[s(s-a)(s-b)(s-c)]

Where s = half of the perimeter of the triangle (in our case =36/2=18)

a, b, & c the length of each side (in our case all sides are equal since it's an equilateral triangle with a perimeter = 36 or each side =36/3 =12)

Now we can apply Heron's formula:

Area =√[18(18-12)(18-12)(18-12] =√[18x6x6x6] =√(3888) = 62.354 cm²

or rounded =62 cm²

ANSWERED AT 26/03/2020 - 10:20 PM

QUESTION POSTED AT 26/03/2020 - 10:20 PM